COST OPTIMIZATION OF JETTY RETROFIT USING VALUE ENGINEERING AND LIFE CYCLE COST ANALYSIS - Ato Muhan Iswidyantara; Bagus Jatmiko; Rina Marlina; Ahmad Faisol; Sultan Al Fahad (Journal of Moeslim Research Technik, 2026)
The increasing demand for sustainable infrastructure has led to a focus on cost optimization in retrofit projects, particularly in maritime infrastructure such as jetties. Sustainable development aims to balance economic growth, environmental protection, and social welfare, highlighting the need for efficient resource utilization. Jetty retrofit projects, crucial for port operations, often face high construction and maintenance costs. This study aims to evaluate the effectiveness of Value Engineering (VE) and Life Cycle Cost Analysis (LCCA) in optimizing the costs of jetty retrofit projects while ensuring long-term sustainability. A mixed-method research design was employed, combining quantitative data from questionnaires and statistical analysis with qualitative insights from field observations and interviews. The study found that integrating VE significantly reduced operational costs, particularly through the substitution of conventional energy systems with renewable energy sources such as solar panels. The application of LCCA demonstrated that long-term savings from energy efficiency could offset higher initial investments. The findings show that the use of VE and LCCA together can achieve cost savings of up to 5.21% and enhance financial viability, with a Benefit-Cost Ratio (BCR) of 2.20, Net Present Value (NPV) of IDR 40.40 billion, and an Internal Rate of Return (IRR) of 46.93%. These results underline the financial and environmental feasibility of green retrofit projects. This research contributes to sustainable infrastructure practices by highlighting cost-effective strategies for jetty retrofitting.